Mechanical and thermal properties of sepiolite strengthened thermoplastic polymer nanocomposites: A comprehensive review - Zahid Iqbal Khan (Elsevier, 2022)
Sepiolite (Si12Mg8O30(OH,F)4].(H2O)4·8H2O) is a valuable filler with an enormous capacity to be used in thermoplastic composites, substituting costly reinforcing fillers, such as graphene and CNTs. Sepiolite strengthened polymers nanocomposite materials have encouraged the field of research and ventures because of their strengthening ability and bio-compatibility in polymer composites. Sepiolite shows remarkable characteristics over various fillers due to its higher specific surface area and channel type structure. Numerous investigations were performed to decide different properties of Sepiolite strengthened polymer composites in various applications, for example, tensile strength, flexural strength, impact strength, stiffness, thermal, flammability, thermo-mechanical, and morphological. This review paper focuses on the mechanical and thermal properties of sepiolite strengthened polymer nanocomposites. Generally, it can be determined that the properties of sepiolite loaded thermoplastic polymer composites mainly depend on filler content, matrix, bond interaction, shape, size of sepiolite particles. Further assessment and development are required to expand its utilization in several applications. These comprise the utilization of nano-size sepiolite made synthetically as functionalized filler in thermoplastics.